Sono-assembly of nanostructures via tyrosine–tyrosine coupling reactions at the interface of acoustic cavitation bubbles. Issue 6 (19th September 2016) - Cavalieri, Francesca; Colombo, Enrico; Nicolai, Eleonora; Rosato, Nicola; Ashokkumar, Muthupandian
Abstract : The reactive and oscillating surface of cavitation microbubbles acts as a catalytic binding site for the coupling of amphiphilic biomolecules. Abstract : This work demonstrates that the reactive and oscillating surface of acoustic cavitation microbubbles acts as a catalytic binding site for the coupling of amphiphilic biomolecules bearing tyrosine moieties at the gas–liquid interface. We show a one-step, controlled ultrasonic process to self assemble tyrosine moieties into highly fluorescent uniformly sized sub-micron particles with new optical and functional properties.